2017
DOI: 10.3390/ijms18061215
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Non-Peptide Mimetics Mapping the Immunodominant Myelin Basic Protein (MBP83–96) Epitope to Function as T-Cell Receptor Antagonists

Abstract: Encephalitogenic T cells are heavily implicated in the pathogenesis of multiple sclerosis (MS), an autoimmune demyelinating disease of the central nervous system. Their stimulation is triggered by the formation of a trimolecular complex between the human leukocyte antigen (HLA), an immunodominant myelin basic protein (MBP) epitope, and the T cell receptor (TCR). We detail herein our studies directed towards the rational design and synthesis of non-peptide mimetic molecules, based on the immunodominant MBP83–96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 75 publications
(97 reference statements)
0
21
0
Order By: Relevance
“…As described here a number of new and upcoming promising therapeutic candidates are becoming available, although their effectiveness in human clinical trials remains to be determined. Recently, it was reported that non-peptide mimetics mapping the MBP [83][84][85][86][87][88][89][90][91][92][93][94][95][96] T cell epitope can function as T cell receptor antagonists, hence such an approach may pave the way to developing alternative and improved immunotherapeutics against MS [189]. With the plethora of information regarding the immunopathophysiology of MS and availability of treatment options and new upcoming treatments, the future holds promise for managing and treating the disease.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…As described here a number of new and upcoming promising therapeutic candidates are becoming available, although their effectiveness in human clinical trials remains to be determined. Recently, it was reported that non-peptide mimetics mapping the MBP [83][84][85][86][87][88][89][90][91][92][93][94][95][96] T cell epitope can function as T cell receptor antagonists, hence such an approach may pave the way to developing alternative and improved immunotherapeutics against MS [189]. With the plethora of information regarding the immunopathophysiology of MS and availability of treatment options and new upcoming treatments, the future holds promise for managing and treating the disease.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…The MBP 83-99 mannan peptide conjugate (50 µg/mouse) was injected in the SJL/J mice subcutaneously into the base of the tail, three times, every two weeks [17]. This conjugate has been shown to induce T cell proliferation and IFN-γ cytokine secretion to the agonist MBP 83-99 peptide in SJL/J mice [17,19,23,24]. Ten to fourteen days after the three injections, spleen cells were isolated, red blood cells were lysed using 0.73% NH 4 Cl, and counted.…”
Section: Mice Conjugates and Immunization Schedulementioning
confidence: 99%
“…In SJL/J mice, immunization with the MBP 83-99 peptide mixed with mycobacterium stimulates autoimmune CD4 + T cells in mice, and induces EAE [7,17]. Major histocompatibility complex (MHC) class II H-2 s haplotype in the SJL/J mouse strain resembles many clinical, histopathological, and immunological characteristics of human MS, thus the SJL/J mouse is regularly used for immunization studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations